Alterations in vaginal microbiota in uterine fibroids patients with ultrasound-guided high-intensity focused ultrasound ablation - Zhang, Ping-Ping; He, Xue-Ping; Tang, Wen; Chen, Han-Wei; Han, Yuan-Yuan (Frontiers in Microbiology, 2023)
Introduction Vaginal microbiota dysbiosis is closely related to diseases of the vagina and uterus. Uterine fibroids (UF) are the most common benign neoplasms of the uterus, and increased diversity in vaginal microbial of UF patients. High-intensity focused ultrasound (HIFU) is effective invasive treatment for fibroids in women who are not good surgical candidates. Whether HIFU of uterine fibroids will cause the change in vaginal microbiota has not been reported. We aimed to investigate the vaginal microbiota of UF patients with/without HIFU treatment using 16S rRNA gene sequencing. Methods Vaginal secretions were collected from 77 UF patients (pre-operative and post-operative) and were used for comparative composition, diversity, and richness analyses of microbial communities. Results The microbial α-diversity was significantly lower in the vaginal of UF patients with HIFU treatment. The relative abundance of some pathogenic bacteria of UF patients with HIFU treatment were significantly decreased in the bacterial phylum and genus level. Proteobacteria were found to be significantly upregulated as a biomarker in the HIFU treatment group in our study. Conclusion These findings might confirm the effectiveness of HIFU treatment from the point of view of microbiota.